Small-scale variability of soil properties and soil–vegetation relationships in patterned ground on different lithologies (NW Italian Alps) - D'AMICO, MICHELE; GORRA, ROBERTA; FREPPAZ, Michele (CATENA, 2015)
Cryogenic patterned ground represents spectacular periglacial landscapes. On the Alps, sorted/nonsorted patterned ground features larger than 1 m, formed by deep seasonal cryoturbation with or without permafrost, occupy exposed, stable surfaces at high altitudes and represent a particularly harsh habitat for plant life. We analyzed soils across transects through typical active patterned ground features (sorted/nonsorted circles and stripes) on four common lithotypes (calcschists, serpentinite, gabbros and gneiss) in the Western Italian Alps, in order to observe the small-scale lateral and depth variability in physico-chemical properties, and their association with cryoturbation, plant cover and species distribution. Cryoturbation was correlated with lateral/vertical textural sorting across features, mostly visible on silt and coarse sand, but with opposite trends on sorted and nonsorted patterned ground types. A strong lateral variability in organic carbon was detected, with high values near the better vegetated rims and low contents in the centers. Exchangeable bases, heavy metals and nutrients followed the same distribution. However, the differences inherited from the parent materials were overwhelming. Climate is the main driver of high altitude ecosystems, reducing total plant cover and causing cryoturbation, which in turn creates strong edaphic gradients over small distances. Plant species and communities are well correlated with edaphic properties inherited from the parent materials, such as exchangeable Ca and heavy metals.